Managing acute promyelocytic leukemia in patients belonging to the Jehovah’s Witness congregation - Anand P. Jillella; Martha L. Arellano; Leonard T. Heffner; Manila Gaddh; Amelia A. Langston; Hanna J. Khoury; Abhishek Mangoankar; Vamsi K. Kota (Hematology Reports, 2017)
Acute promyelocytic leukemia (APL) is a hyper-acute leukemia and presents with cytopenias and disseminated intravascular coagulation. Jehovah’s Witnesses with APL offer a unique challenge during induction by refusing transfusion and pose a difficult challenge in this curable disease. Our focus over the last 8 years has been decreasing early deaths in APL in both academic and community centers. As a result we have extensive experience in APL induction with a proven improvement in early deaths. Three patients with APL belonging to the Jehovah’s Witness congregation were treated in our practice and published literature in treating Witnesses with APL was reviewed. It is highly imperative to prevent induction mortality in this patient population. The goal of treatment among the Witnesses is to prevent death during induction and subsequently cure them. We discuss the management and proactive measures to prevent induction mortality in this most curable blood cancer.